Association of gene mutations with time‐to‐first treatment in 384 treatment‐naive chronic lymphocytic leukaemia patients. (26th June 2019) - Hu, Boyu; Patel, Keyur P.; Chen, Hsiang‐Chun; Wang, Xuemei; Luthra, Rajyalakshmi; Routbort, Mark J.; Kanagal‐Shamanna, Rashmi; Medeiros, L. Jeffrey; Yin, C. Cameron; Zuo, Zhuang; Ok, Chi Y.; Loghavi, Sanam; et al.
Summary: This study correlated somatic mutation results and known prognostic factors with time‐to‐first treatment (TTFT) in 384 treatment‐naïve (TN) chronic lymphocytic leukaemia (CLL) patients to help determine disease‐specific drivers of early untreated CLL. CLL DNA from either peripheral blood or bone marrow underwent next generation targeted sequencing with a 29‐gene panel. Gene mutation data and concurrent clinical characteristics, such as Rai/Binet stage, fluorescence in situ hybridisation (FISH), ZAP70/CD38, karyotype and IGHV mutation, status were analysed in univariable and multivariable analyses to identify associations with TTFT. TTFT was defined as time from diagnosis to initial treatment. In univariable analyses, mutated ATM ( P  < 0·001), NOTCH1 ( P  < 0·001) and SF3B1 ( P  = 0·002) as well as unmutated IGHV ( P  < 0·001), del(11q) ( P  < 0·001) and trisomy 12 ( P  < 0·001) by hierarchal FISH and advanced Rai ( P  = 0·05) and Binet ( P  < 0·001) stages were associated with shorter TTFT. Importantly, del(17p), mutated TP53 and complex karyotype were not associated with shorter TTFT. In a reduced multivariable analysis, mutated ATM ( P  < 0·001) and unmutated IGHV status ( P  < 0·001) remained significant, showing their importance in early leukaemogenesis. High‐risk prognostic markers such as del(17p), mutated TP53 and complex karyotype, were not correlated with TTFT, suggesting that these abnormalities have limited roles in early disease progression but are more important in relapsed CLL.